Substitutes for Cash in the Panic of 1907 - Andrew, A. Piatt (Quarterly Journal of Economics, 1908)
Journal Article Substitutes for Cash in the Panic of 1907 Get access A. Piatt Andrew A. Piatt Andrew Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 22, Issue 4, August 1908, Pages 497–516, https://doi.org/10.2307/1884914 Published: 01 August 1908